Pemberdayaan Masyarakat Melalui Pelatihan Labeling Kemasan Produk UMKM Pada Ibu-Ibu PKK Dusun Sukajadi - Rulik Setiani; Yogi Ferdiyanto; Dori Prasetyo; Cahya Novita Sari; Nabila Umi Khoirunisa; Septiana Sari (LP3M Universitas Putra Bangsa, 2023)
The aim of implementing community service in the form of training is so that PKK women as micro business product has expertise in how to make good and attractive packaging, labels and marketing. There were 15 participants who attended this activity, this activity was held one day on February 27 2023 at the Sukajadi district, the activity was held from 13.00-17.00 WIB. This activity is carried out starting from making preparations, namely by observing what problems we can help with, then providing information about the activities we want to do and then carrying out the activities we have planned and prepared. In this implementation activity, our PkM UMKO team provided material regarding labeling to micro business product actors who are members of the PKK women's group. In this training the team community service presents 2 materials, namely: digital marketing and the importance of labeling on products. The final activity is evaluating the results of community service activities in the form of training for micro business product actors.